2020
DOI: 10.3389/fmed.2020.00270
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, Fetal, and Placental Selectins in Women With Pre-eclampsia; Association With the Renin-Angiotensin-System

Abstract: Selectins [endothelial (E), platelet (P), and leucocytes (L)] are a class of cell adhesion molecules, stimulated in response to inflammation. Pre-eclampsia is characterized by inflammation, and angiotensin II is pro-inflammatory. We hypothesized that circulating maternal and fetal concentrations and placental expression of selectins would be increased in women with pre-eclampsia and would be associated with the angiotensin receptors (AT1R and AT2R). Maternal and fetal blood and placental tissue was collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(65 reference statements)
0
10
1
Order By: Relevance
“…Unlike sE-selectin, the serum concentrations of soluble P-selectin (sP-selectin) and soluble L-selectin (sL-selectin) do not seem to be as reliable markers of endothelial dysfunction and damage in PE as sE-selectin. In turn, while sP-selectin serum levels were found to be increased in patients with PE in some previous studies [37,50], it was not confirmed in the latest one by Mistry et al [43]. Moreover, conflicting results have been reported regarding the concentration of sL-selectin in patients with PE [37,43].…”
Section: E-selectin P-selectin L-selectinmentioning
confidence: 87%
See 4 more Smart Citations
“…Unlike sE-selectin, the serum concentrations of soluble P-selectin (sP-selectin) and soluble L-selectin (sL-selectin) do not seem to be as reliable markers of endothelial dysfunction and damage in PE as sE-selectin. In turn, while sP-selectin serum levels were found to be increased in patients with PE in some previous studies [37,50], it was not confirmed in the latest one by Mistry et al [43]. Moreover, conflicting results have been reported regarding the concentration of sL-selectin in patients with PE [37,43].…”
Section: E-selectin P-selectin L-selectinmentioning
confidence: 87%
“…In turn, while sP-selectin serum levels were found to be increased in patients with PE in some previous studies [37,50], it was not confirmed in the latest one by Mistry et al [43]. Moreover, conflicting results have been reported regarding the concentration of sL-selectin in patients with PE [37,43].…”
Section: E-selectin P-selectin L-selectinmentioning
confidence: 87%
See 3 more Smart Citations